Bank Competition - When is it Good? - Christa Hainz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
The effects of bank competition and institutions on credit markets are usually studied separately although both factors are interdependent. We study the effect of bank competition on the choice of contracts (screening versus collateralized credit contract) and explicitly capture the impact of the institutional environment. Most importantly, we show that the effects of bank competition on collateralization, access to finance, and social welfare depend on the institutional environment. We predict that firms' access to credit increases in bank competition if institutions are weak but bank competition does not matter if they are well-developed.
urn:nbn:de:bvb:19-epub-13308-0
Keywords: D82; G21; K00; 330; Bank competition; collateralization; screening; incentives